Investigation of the impacts of ethyl lactate based Fenton treatment on soil quality for polycyclic aromatic hydrocarbons (PAHs)-contaminated soils - Gan, Suyin; Yap, Chiew Lin; Ng, Hoon Kiat; Venny (Journal of hazardous materials, 2013)
•Accumulation of oxy-PAHs was observed, with ATQ as the most abundant compound.•ATQ had lower accumulation in ethyl lactate based compared to ethanol based Fenton.•Both positive and negative impacts on soil physicochemical properties were recorded.•For revegetation, the treatment was most suitable for soil with native pH≳6.2. This study aims to investigate the impacts of ethyl lactate (EL) based Fenton treatment on soil quality for polycyclic aromatic hydrocarbons (PAHs)-contaminated soils. Accumulation of oxygenated-polycyclic aromatic hydrocarbons (oxy-PAHs) was observed, but quantitative measurement on the most abundant compound 9,10-anthraquinone (ATQ) showed lower accumulation of the compound than that reported for ethanol (ET) based Fenton treatment. In general, as compared to conventional water (CW) based Fenton treatment, the EL based Fenton treatment exerted either a lower or higher negative impact on soil physicochemical properties depending on the property type and shared the main disadvantage of reduced soil pH. For revegetation, EL based Fenton treatment was most appropriately adopted for soil with native pH≳6.2 in order to obtain a final soil pH≳4.9 subject to the soil buffering capacity.